Rising BRICs and Changes in Sub-Saharan Africa's Business Cycle Patterns - Diallo, Oumar (IMF Working Papers; Working Paper ;, 2014)
This paper assesses the extent to which Sub-Saharan Africa (SSA)'s business cycle is synchronized with that of the rest of the world (RoW). Findings suggest that SSA's business cycle has not only moved in the same direction as that of the RoW, but has also gradually drifted away from the G7 in favour of the BRICs. Trade with the BRICs turns out to be the strongest driver of this shift. Much of this impact unfolds through aggregate demand impulse from trade. As fiscal policy stances in SSA and the BRICs are not synchronized, they have not caused cyclical output correlation between these two groups of countries. Also, financial openness, which is at a very early stage across most SSA countries, has acted as a neutral force.